WEEKLY STATUS REPORT - STATE GOVERNMENT RELATIONS. - MOZINGO RL (Tufts Archival Research Center, 2007)
Weekly status report on state government relations from R.L. Mozingo to T.J. Payne. Traces the progress of legislation on the state level. Divides issues into taxes, marketing sales and advertisements restrictions, product liability, Gray market, smoking restrictions, ingredients, MSA legislation, youth, and divestment.